Oral Health Status, Oral Hygiene Practices, and Factors Affecting Dental Treatment Utilization among Pregnant Women in Dubai - Sosham John (Karger Publishers, 2021)
Objective: Oral health is an integral part of preventive healthcare for pregnant women. This study aimed to determine the oral health problems and oral hygiene practices and identify the factors affecting dental treatment utilization among a representative population of pregnant women in Dubai. Methods: A cross-sectional study was conducted using data from anonymous structured questionnaires filled by 1,450 pregnant women attending primary health centers across different geographical locations in Dubai. Results: Of the 1,450 women, 97.8% brushed at least once a day. At least one dental problem during pregnancy was reported by 49.9%, but dental attendance during pregnancy was only 17.4%. Factors associated with dental visits were nationality, previous pregnancy, oral health problems, brushing habits, routine dental visits, and professional advice on oral care. The odds of dental attendance increase for UAE national women by 1.48, women who had other children before the current pregnancy by 1.35, those having oral health problems by 1.85, those who brush more than once a day by 1.51, those who visited the dentist routinely at least once a year by 1.92, and those who received oral health education by 2.82. The most cited reasons for not going to the dentist were no perceived dental problem (51.8%) and concerns regarding the safety of dental treatment during pregnancy (33.9%). Discussion/Conclusion: In spite of acceptable oral hygiene practices, a significant number of pregnant women (49.9%) experience dental problems. However, only a few women (17.4%) visit the dentist during their pregnancy. It is critical to design and implements strategic oral health programs for pregnant women in Dubai.